2019
DOI: 10.1177/1553350619853134
|View full text |Cite
|
Sign up to set email alerts
|

“Targeted Percutaneous Vertebroplasty” Versus Traditional Percutaneous Vertebroplasty for Osteoporotic Vertebral Compression Fracture

Abstract: Objective. In this randomized, nonblinded, controlled study, the feasibility and precision of “targeted percutaneous vertebroplasty” (“targeted PVP”) for osteoporotic vertebral compression fracture (OVCF) was evaluated. Methods. A total of 42 patients, aged 50 to 87 years, with OVCF were randomly divided into 2 groups: A and B. Group A underwent “targeted PVP,” and group B underwent traditional PVP with the guidance of C-arm fluoroscopy. Fluoroscopy times for skin puncture points (FTSPP), total radiation doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The main indications for PVP for the surgery include the following: (1) Acute OVCF (Magnetic resonance imaging [MRI] on T1-weighted images showed a low signal. MRI on T2-weighted images and short tau inversion recovery sequences showed high signal; (2) VAS (visual analogue scale) ≥6; (3) The patient refused to receive conservative treatment [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main indications for PVP for the surgery include the following: (1) Acute OVCF (Magnetic resonance imaging [MRI] on T1-weighted images showed a low signal. MRI on T2-weighted images and short tau inversion recovery sequences showed high signal; (2) VAS (visual analogue scale) ≥6; (3) The patient refused to receive conservative treatment [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, targeted PVP appeared to achieve lower skin positioning fluoroscopy times and lower total fluoroscopy times. It used a lower dose, had a shorter operation time, and was more precise than traditional PVP [4]. Targeted PVP also revealed a lower incidence of cement leakage.…”
Section: Resultsmentioning
confidence: 97%
“…Current literature states that the incidence of KD is around 7% to 37% in elderly individuals. The population in developed countries is aging and KD is a potential complication in up to one-third of OVCFs, which requires discussing an appropriate therapeutic approach for these patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. KD usually affects the lower thoracic or upper lumbar region of the spine and it usually involves only a single vertebra [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some novel ultrasound naviagation technologies have been used in PVP surgery. Xu, et al [14] have reported a "Targeted Percutaneous Vertebroplasty" that is a 3D model of fractured vertebra based on preoperative CT scanning data is built preoperatively, and with the help of preoperative digital design, bilateral skin entry points, needle trajectory, and needle insertion depth are established. However, preoperative CT scanning is not exactly the same posture as that in the real operative procedure, whose deviation could result in serious errors for puncture complications.…”
Section: Resultsmentioning
confidence: 99%